2018
DOI: 10.1007/s10936-018-9558-7
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the Conflicting Results of Psycholinguistic Experiments: How to Resolve Them with the Help of Statistical Meta-analysis

Abstract: This paper proposes the use of the tools of statistical meta-analysis as a method of conflict resolution with respect to experiments in cognitive linguistics. With the help of statistical meta-analysis, the effect size of similar experiments can be compared, a well-founded and robust synthesis of the experimental data can be achieved, and possible causes of any divergence(s) in the outcomes can be revealed. This application of statistical meta-analysis offers a novel method of how diverging evidence can be dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For instance, meta-analyses are a popular method of research synthesis in applied linguistics (Ellis, 2015;Norris & Ortega, 2007). By contrast, meta-analysis seems less well known in psycholinguistics, given that a recent paper introduced meta-analysis as a "novel method" to the field (Rákosi, 2018). Across academic disciplines, different meta-analyses have looked at the persuasive impact of verbal metaphors (e.g., Rákosi, 2018;Sopory & Dillard, 2002, Van Stee, 2018.…”
Section: Application 4: Quantitative Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, meta-analyses are a popular method of research synthesis in applied linguistics (Ellis, 2015;Norris & Ortega, 2007). By contrast, meta-analysis seems less well known in psycholinguistics, given that a recent paper introduced meta-analysis as a "novel method" to the field (Rákosi, 2018). Across academic disciplines, different meta-analyses have looked at the persuasive impact of verbal metaphors (e.g., Rákosi, 2018;Sopory & Dillard, 2002, Van Stee, 2018.…”
Section: Application 4: Quantitative Meta-analysismentioning
confidence: 99%
“…By contrast, meta-analysis seems less well known in psycholinguistics, given that a recent paper introduced meta-analysis as a "novel method" to the field (Rákosi, 2018). Across academic disciplines, different meta-analyses have looked at the persuasive impact of verbal metaphors (e.g., Rákosi, 2018;Sopory & Dillard, 2002, Van Stee, 2018. These meta-analyses consistently found that metaphors have a statistically small effect on persuasion, and that effect sizes differ between metaphors, topics, and other conditions.…”
Section: Application 4: Quantitative Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we expected that the framing effect of metaphor might also depend on the type of metaphor featured in the first premise of the argument. In fact, conventional metaphors are not perceived as metaphors, bearing a status similar to polysemous literal term ( Carston, 2002 ; Giora, 2003 ; Bowdle and Gentner, 2005 ; Kenett et al, 2018 ), and unconsciously act as triggers of “systems of commonplaces” or background of associated beliefs ( Black, 1954 ; Coulson, 2001 ; Lakoff, 2004 ; Thibodeau and Boroditsky, 2011 , 2013 ). Novel metaphors, however, are consciously processed as metaphors and require new, original and creative interpretations ( Indurkhya, 2007b , 2010 ; Kenett et al, 2018 ).…”
Section: Current Researchmentioning
confidence: 99%
“…The mapping of properties from the source to the target implicitly forces the interpreter to consider the target in a specific perspective. Therefore, different metaphorical views might seriously affect one’s reasoning and evaluation of arguments ( Lakoff, 2004 ; Goatly, 2007 ; Thibodeau and Boroditsky, 2011 , 2013 ; Steen et al, 2014 ; Semino et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%